Laminate for flexible display, and flexible display

By adjusting the surface free energy polarity term of the adhesive layer, using an acrylic adhesive, and adding a low-polar additive, the problem of offset and display defects in the bending of the flexible display is solved, and excellent bending and visual recognition are achieved.

CN119585380AInactive Publication Date: 2025-03-07아티엔스가부시키가이샤 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380054989.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-10
Filing Date
2023-07-21
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the repeated bending and high-speed bending of the flexible display, the existing adhesive layer is prone to be offset by the adhesive, the adhesive layer floats or foams, resulting in display defects.

Method used

By adjusting the polarity component of the surface free energy of the adhesive layer to be less than 0.5 mN/m, using an acrylic adhesive, and adding a low-polar additive to the adhesive, ensuring that the mass of the adhesive layer is between 10 g/m2 and 100 g/m2.

Benefits of technology

It is achieved that the adhesive is not offset and the adhesive layer floats or foams under repeated bending and high-speed bending conditions, ensuring excellent bending and visual recognition of the display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585380A_ABST
    Figure CN119585380A_ABST
Patent Text Reader

Abstract

In the present disclosure, provided is a laminate for a flexible display, comprising an adhesive layer formed of an acrylic adhesive on a light-transmitting flexible substrate, the acrylic adhesive comprising: an acrylic copolymer containing repeating units derived from an alkyl (meth) acrylate having an alkyl group having 4 or more carbon atoms; and a low polarity additive. A flexible display including the laminate is also provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an adhesive layer for forming a laminate, and a laminate having the adhesive layer, wherein the laminate is a laminate for a flexible display including a light-transmitting flexible substrate and an adhesive layer, and sequentially includes the light-transmitting flexible substrate, the adhesive layer, and a polarizing plate. The laminate can be used for a flexible display.

[0002] In recent years, input devices that combine image display devices such as liquid crystal display (LCD) or organic electroluminescence (EL) display (organic light emitting diode (OLED)) with touch screens have become popular. The transparent conductive film used in the touch screen is laminated on a supporting glass or other member via an adhesive layer. In addition, the polarizing plate film used in the image device is attached to the liquid crystal module or organic EL module via an adhesive layer.

[0003] As the image display device, flat panel displays using glass substrates are the mainstream, but in recent years, flexible displays such as foldable displays and rollable displays using flexible substrates such as plastics have been developed. Compared with the previous flat panel displays using glass substrates, such flexible displays have various advantages such as light weight, thickness, flexibility, and excellent design.

[0004] In order to be used in a foldable display, adaptability (bendability) corresponding to the bending of the display is required. Generally speaking, as bendability, it is required to have a property that does not cause bubbling, floating or peeling when repeatedly bent (dynamic bendability).

[0005] In order to solve these problems, Patent Document 1 discloses an optically transparent adhesive sheet, characterized in that it contains a resin syrup produced by partially polymerizing a (meth)acrylate monomer, and a photoinitiator, and the storage elastic modulus of the adhesive layer is 1.0×106Pa to 1.0×107Pa at 25°C and 1Hz. In addition, Patent Document 2 discloses an adhesive layer formed of an adhesive containing a base polymer, a photocurable compound, and a photoinitiator.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-517800

[0009] Patent Document 2: Japanese Patent Application Publication No. 2020-097737 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, in such conventional adhesive layers, when a flexible display is repeatedly bent, the adherends bonded by the adhesive layer may shift, or the adhesive layer exposed from the end may come into contact with surrounding members, deteriorating the bendability, and the bendability cannot be said to be sufficient.

[0012] Furthermore, in recent years, in foldable displays, as a light-transmitting flexible substrate, a colorless polyimide with overwhelming mechanical properties and made transparent can be used. As a result, the durability required for the adhesive layer becomes more stringent, but if the laminated body with the adhesive layer and the colorless polyimide bonded is repeatedly bent, there are the following problems: floating occurs in the adhesive layer in the bent portion, causing the offset of the adherends, or foaming occurs in the adhesive layer, causing whitening due to bubbles. In addition, even products that are considered to have no problems in the usual repeated bending test will have the following problems when bent at a higher speed than expected: offset of the adherends, floating of the adhesive layer, and foaming in the adhesive layer will cause problems during display.

[0013] Therefore, the purpose of the present disclosure is to provide a laminated body in which the adherends after bonding will not be offset and the adhesive layer will not be exposed from the end, regardless of repeated bending or high-speed bending. Furthermore, the purpose is to provide a laminated body for a flexible display that will not cause display defects at the bent portion even when a high-polarity substrate such as colorless polyimide is used as a light-transmitting flexible substrate, and a flexible display with excellent visibility.

[0014] Technical means of solving problems

[0015] The present inventors have made intensive studies and found that the problems can be solved in the following aspects.

[0016] That is, the present disclosure provides a laminate for a flexible display, comprising an adhesive layer on a light-transmitting flexible substrate, wherein the laminate for a flexible display is characterized in that the polar term component of the surface free energy of the light-transmitting flexible substrate calculated based on the contact angle of water and the contact angle of diiodomethane and based on the Owens-Wendt-Rabel-Kaelble method (OWRK method) is 3.0 mN / m or more, the polar term component of the surface free energy of the adhesive layer calculated based on the contact angle of water and the contact angle of diiodomethane and based on the OWRK method is 0.5 mN / m or less, and the mass per unit area of ​​the adhesive layer is 10 g / m 2 ~100g / m 2 The adhesive layer is formed by an acrylic adhesive, and the acrylic adhesive comprises: an acrylic copolymer, wherein in 100% by mass of the acrylic copolymer, 25% by mass or less of repeating units derived from a hydroxyl-containing monomer, 10% by mass or less of repeating units derived from an acid-containing monomer, 15% by mass or less of repeating units derived from an amide group-containing monomer, 15% by mass or less of repeating units derived from an amino group-containing monomer, and 75% to 90% by mass of repeating units derived from an alkyl (meth)acrylate having an alkyl group with 4 or more carbon atoms are contained; and a low-polarity additive.

[0017] Effects of the Invention

[0018] The present disclosure can provide a laminated body that does not cause deviation of adherends after bonding and does not expose the adhesive layer from the end, regardless of repeated bending or high-speed bending. Furthermore, a laminated body for a flexible display that does not cause display defects at a bent portion, and a flexible display with excellent visibility can be provided even when a highly polar substrate such as colorless polyimide is used as a light-transmitting flexible substrate.

[0019] Furthermore, by using the laminated body of the present disclosure, a flexible display having excellent visibility can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] [ Figure 1 ] is a schematic cross-sectional view partially showing a stacked body according to one embodiment of the present disclosure.

[0021] [ Figure 2 ] is a schematic cross-sectional view partially showing a flexible display as an example of use of a laminated body as one embodiment of the present disclosure. DETAILED DESCRIPTION

[0022] Hereinafter, structural examples of the laminated body and the flexible display of the present disclosure will be described, but the present invention is not limited thereto.

[0023] In addition, the numerical range determined by using "to" in this specification is set to include the numerical values ​​recorded before and after "to" as the range of the lower limit and upper limit. In addition, "film" or "sheet" is not distinguished according to thickness. In other words, the "sheet" in this specification also includes a thin film-like sheet, and the "film" in this specification also includes a sheet-like film with thickness.

[0024] The adherend refers to the other side to which the adhesive layer of the adhesive sheet is attached, for example, in the case of a laminate for a flexible display including a light-transmitting flexible substrate, an adhesive layer, and a polarizing plate in this order, it refers to the light-transmitting flexible substrate and the polarizing plate.

[0025] Unless otherwise specified, various components mentioned in the present specification may be used alone or in combination of two or more.

[0026] 《Adhesive layer for flexible display》

[0027] The adhesive layer used in the laminate of the present disclosure is characterized in that a polar term component of surface free energy calculated based on the OWRK method from the contact angle of water and the contact angle of diiodomethane is 0.5 mN / m or less.

[0028] Therefore, no deviation of the adherends after bonding occurs regardless of repeated bending or high-speed bending, and the adhesive layer does not protrude from the ends. Furthermore, even when a highly polar substrate such as colorless polyimide is used as the light-transmitting flexible substrate, no display defects occur at the bent portion.

[0029] <Polar component of surface free energy>

[0030] The polar term component of the surface free energy is less than 0.5mN / m. The smaller the polar term component of the surface free energy of the adhesive layer, the more preferred, preferably more than 0mN / m. In addition, preferably less than 0.3mN / m, more preferably less than 0.2mN / m. By adjusting the polar term component to less than 0.5mN / m, it is possible to obtain an adhesive layer in which the bent portion will not whiten regardless of repeated bending or high-speed bending, and the offset of the adherends after bonding will not occur. Although the mechanism for obtaining this effect is unclear, it is speculated that the reason is that even if the adhesive layer exerts strong adhesion to the adherend, the strong intermolecular attraction generated by the dipole interaction does not contribute to the performance of the adhesion, so that when the shear force is applied by bending, the adhesive layer will not peel off from the adherend and follow.

[0031] The polar term component of the surface free energy can be controlled to 0.5 mN / m or less by reducing the polarity of the resin used in the adhesive and by adding a low-polarity additive that is preferentially present on the surface after coating.

[0032] The surface free energy was calculated based on the contact angle of water and the contact angle of diiodomethane at 25° C. according to the OWRK method.

[0033] Specifically, the contact angle of each liquid is measured 1 second after the droplet volume is set to 1 μl. The device used in the contact angle measurement is not particularly limited, and examples thereof include the automatic contact angle meter DM-501Hi manufactured by Kyowa Interface Science Co., Ltd. The polar term component of the surface free energy is calculated together with the dispersion term component using the OWRK method.

[0034] <Gel fraction>

[0035] The gel fraction of the adhesive layer disclosed herein is preferably 55% to 90% by mass, and more preferably 60% to 80% by mass. If the gel fraction is 55% by mass or more, the cohesive force of the adhesive is improved, a tough adhesive layer is obtained, and the adhesive layer is less likely to be exposed from the end when bent. If it is 90% by mass or less, the stress relaxation of the adhesive is improved, a soft adhesive layer is easily obtained, the adhesion is improved, and the deviation of the adherends when bent can be further suppressed.

[0036] [Gel fraction measurement method]

[0037] The gel fraction can be determined as the insoluble content in a solvent such as ethyl acetate. Specifically, as shown in the following formula 1, it is determined as the mass fraction (unit: mass %) of the insoluble content after the adhesive layer is immersed in ethyl acetate at 50°C for one day relative to the adhesive layer before the immersion.

[0038] (Formula 1)

[0039] Gel fraction (mass %) = (Y / X) × 100

[0040] X = mass of adhesive layer before immersion (g)

[0041] Y = Mass of adhesive layer after immersion (g)

[0042] Generally speaking, the gel fraction of a polymer is equal to the degree of crosslinking, and the more crosslinked parts in the polymer, the greater the gel fraction. The gel fraction (the amount of crosslinked structure introduced) can be adjusted to a desired range according to the method of introducing the crosslinked structure, the type and amount of the crosslinking agent, etc.

[0043] <Adhesive>

[0044] The adhesive layer is formed of an adhesive.

[0045] The resin system of the adhesive is an acrylic adhesive. By using an acrylic adhesive as the adhesive, the polar term component of the surface free energy is adjusted to 0.5 mN / m or less, and various performance balances can be easily achieved.

[0046] [Acrylic adhesive]

[0047] The acrylic adhesive has an acrylic copolymer as a (meth)acrylate polymer as a main component, contains a low-polarity additive described below, and may contain a hardener and other additives as needed. The so-called (meth)acrylate includes acrylate and methacrylate. The so-called monomer is a monomer having an ethylenically unsaturated group.

[0048] (Acrylic copolymer)

[0049] The acrylic copolymer is a polymer containing one or two or more monomers of acrylic monomers such as (meth)acrylic acid alkyl esters. Examples of the alkyl (meth)acrylate include those having a linear or branched alkyl group such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, and those having a cyclic alkyl group such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate.

[0050] Preferably, a monomer containing a unit derived from (meth) acrylic acid (ester) having a functional group is copolymerized in the acrylic copolymer. In addition to imparting cohesive force to the adhesive layer by including a functional group, the cohesive force of the adhesive layer can be further increased by using a hardener in the adhesive, thereby easily suppressing exposure during bending.

[0051] The functional group of the (meth)acrylate having a functional group is preferably at least one selected from a carboxyl group, a hydroxyl group, an amino group, an amide group, an oxyalkylene group, an epoxy group and an isocyanate group, more preferably at least one selected from a carboxyl group, a hydroxyl group, an amino group and an amide group, and further preferably at least one or both selected from a carboxyl group and a hydroxyl group.

[0052] Examples of the monomer (or acid-containing monomer) unit having a carboxyl group include acrylic acid and methacrylic acid.

[0053] The monomer unit having a hydroxyl group is a repeating unit derived from a monomer having a hydroxyl group. Examples of the monomer having a hydroxyl group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxypropyl (meth)acrylate, (meth)acrylic acid [(mono-, di-, or poly-)alkylene glycol] such as (meth)acrylate mono(diethylene glycol), and (meth)acrylic acid lactones such as (meth)acrylate monocaprolactone.

[0054] Examples of monomer units having an amino group include repeating units derived from monomers containing a primary amino group such as aminomethyl (meth)acrylate and aminoethyl (meth)acrylate, monomers containing a secondary amino group such as tert-butylaminoethyl (meth)acrylate, monomers containing a tertiary amino group such as ethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate, and monomers containing an amino group such as allylamine, vinylpyridine, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, and vinyloxazole.

[0055] Examples of monomer units having an amide group include cyclic amides such as (meth)acrylamide, N-vinyl lactams, vinyl morpholine, and (meth)acryloyl morpholine, N-vinyl carboxylic acid amides such as N-vinyl formamide and N-vinyl acetamide, acrylamide, and N,N-dimethylacrylamide. N-vinyl lactams are monomers having a cyclic lactam ring, and examples thereof include N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-ε-caprolactam, and compounds having structures in which one or more of the hydrogen atoms of these are substituted with substituents. Examples of substituents include alkyl groups having 1 to 20 carbon atoms, alkyl groups having 2 to 20 carbon atoms, aryl groups having 6 to 20 carbon atoms, alkoxy groups having 1 to 20 carbon atoms, carboxyl ester groups having 3 to 20 carbon atoms, and amino groups having 1 to 20 carbon atoms, and do not include acidic groups such as hydroxyl groups or carboxylic acid (salt) groups, sulfonic acid (salt) groups, and hypophosphite (salt) groups.

[0056] Examples of the monomer unit having an oxyalkylene group include methoxytriethylene glycol (meth)acrylate, methoxypolyethylene glycol #400 (meth)acrylate, methoxydipropylene glycol (meth)acrylate, methoxytripropylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, ethyl carbitol (meth)acrylate, 2-ethylhexyl carbitol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenoxydiethylene glycol (meth)acrylate.

[0057] As a monomer unit which has an isocyanate group, 2-isocyanateethyl(meth)acrylate, 3-isocyanatepropyl(meth)acrylate, 4-isocyanatebutyl(meth)acrylate, etc. are mentioned.

[0058] Examples of the monomer unit having an epoxy group include repeating units derived from a monomer having a glycidyl group such as glycidyl (meth)acrylate.

[0059] The hydroxyl-containing monomer is 25% by mass or less in 100% by mass of the acrylic copolymer, and more preferably 20% by mass or less. In addition, in the present disclosure, a monomer being n% by mass (or comprising n% by mass) in 100% by mass of the acrylic copolymer means that the repeating unit derived from the monomer accounts for n% by mass of the copolymer. In addition, a monomer being n% by mass or less (or comprising n% by mass or less) in 100% by mass of the acrylic copolymer may also include an embodiment in which the monomer is 0% by mass.

[0060] The acid-containing monomer is 10% by mass or less, and more preferably 7% by mass or less, in 100% by mass of the acrylic copolymer.

[0061] The amide group-containing monomer is 15% by mass or less, more preferably 10% by mass or less, and most preferably 7% by mass or less in 100% by mass of the acrylic copolymer.

[0062] The amino group-containing monomer is 15% by mass or less, more preferably 10% by mass or less, and most preferably 7% by mass or less in 100% by mass of the acrylic copolymer.

[0063] The ratio of the oxyalkylene group-containing monomer is preferably 30% by mass or less, more preferably 15% by mass or less, and most preferably 12% by mass or less.

[0064] Among other monomers copolymerizable with the acrylic monomer, the monomer having a water / octanol partition coefficient log Kow of 2.22 or less at 25° C. and the monomer miscible with water are preferably 20% by mass or less, more preferably 15% by mass or less, and most preferably 12% by mass or less.

[0065] The monomers described in the paragraphs may be 0% by mass or more (i.e., may be 0% by mass) in 100% by mass of the acrylic copolymer. For example, in 100% by mass of the acrylic copolymer, the hydroxyl-containing monomer may be 0.5% by mass or more, and the acid-containing monomer may be 0.2% by mass or more. In one embodiment, in 100% by mass of the acrylic copolymer, the hydroxyl-containing monomer may be 0.5% by mass or more, and the acid-containing monomer may be 0.2% by mass or more, and the other monomers described in the paragraphs may be 0% by mass or more.

[0066] The (meth)acrylic acid alkyl ester having an alkyl group with 4 or more carbon atoms is 75% to 90% by mass, preferably 78% to 88% by mass, in 100% by mass of the acrylic copolymer. By using the above-mentioned monomer as the main component, the polarity of the acrylic copolymer is reduced. The alkyl group typically has 16 or less carbon atoms.

[0067] The (meth)acrylic acid copolymer may optionally have other monomer units in addition to the monomer units. Other monomers may be copolymerizable with the acrylic acid monomers, for example, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristic acid, vinyl palmitate, vinyl stearate, vinyl cyclohexanecarboxylate, vinyl benzoate, or vinyl carboxylate or styrene. Among these, vinyl acetate, vinyl propionate, and vinyl butyrate are hydrophilic when their water / octanol partition coefficient log Kow at 25° C. is less than 2.30, so in order to reduce the polarity of the acrylic copolymer, it is preferably to reduce the ratio as described below.

[0068] The log Kow value can be calculated, for example, based on the structural formula of the monomer using the HSPiP software (Steven Abbott, Hiroshi Yamamoto).

[0069] (Manufacture of acrylic copolymer)

[0070] The acrylic copolymer can be produced by polymerizing a monomer mixture.

[0071] The polymerization can be a known polymerization method such as solution polymerization, bulk polymerization, emulsion polymerization, suspension polymerization, etc., preferably solution polymerization. The solvent used in solution polymerization is preferably acetone, methyl acetate, ethyl acetate, toluene, xylene, anisole, methyl ethyl ketone, cyclohexanone, etc.

[0072] The polymerization temperature is preferably a boiling point reaction of 60° C. to 120° C. The polymerization time is preferably about 5 hours to 12 hours.

[0073] The polymerization initiator used in the polymerization is preferably a free radical polymerization initiator. Free radical polymerization initiators are generally peroxides and azo compounds.

[0074] Examples of peroxides include dialkyl peroxides such as di-tert-butyl peroxide, dicumyl peroxide, tert-butylcumyl peroxide, α,α′-bis(tert-butylperoxy-m-isopropyl)benzene, and 2,5-di(tert-butylperoxy)hexyne-3-yl.

[0075] Peroxyesters such as tert-butyl peroxybenzoate, tert-butyl peroxyacetate, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane; ketone peroxides such as cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, and methylcyclohexanone peroxide;

[0076] Peroxy ketals such as 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)propane, 1,1-bis(tert-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, and n-butyl-4,4-bis(tert-butylperoxy)valerate;

[0077] Hydroperoxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, and 2,5-dimethylcyclohexane-2,5-dihydroperoxide;

[0078] Diacyl peroxides such as benzoyl peroxide, decanoyl peroxide, lauroyl peroxide, and 2,4-dichlorobenzoyl peroxide;

[0079] Peroxydicarbonates such as bis(tert-butylcyclohexyl)peroxydicarbonate and the like.

[0080] Examples of the azo compound include 2,2'-azobisisobutyronitrile (abbreviation: AIBN (2,2'-azobisisobutyronitrile)), 2,2'-azobis(2-methylbutyronitrile), and the like;

[0081] 2,2'-azobisvaleronitrile such as 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile); 2,2'-azobispropiononitrile such as 2,2'-azobis(2-hydroxymethylpropiononitrile);

[0082] 1,1'-Azobis(cyclohexane-1-carbonitrile) and other 1,1'-azobis-1-alkanenitrile and the like.

[0083] The polymerization initiator is used in an amount of preferably 0.01 to 10 parts by mass, more preferably 0.1 to 2 parts by mass, based on 100 parts by mass of the monomer mixture.

[0084] (Mass average molecular weight (Mw))

[0085] The mass average molecular weight of the acrylic copolymer is preferably 800,000 to 1,800,000, more preferably 1,000,000 to 1,500,000. If it is within the range of 800,000 to 1,800,000, the cohesive force is further improved, and the adhesive layer is not easy to be exposed from the end when bent. In addition, the mass average molecular weight is a value converted to polystyrene measured by gel permeation chromatography (GPC).

[0086] (Hardener)

[0087] The acrylic adhesive preferably contains a hardener. The hardener prepared in the adhesive is preferably a hardener that reacts with the functional group of the monomer having the functional group by heat or the like to form a bond. The preparation of the hardener can improve the cohesive force of the adhesive layer, and further improve the durability and stain resistance.

[0088] As a hardener, it can be appropriately selected from known crosslinking agents such as isocyanate compounds, epoxy compounds, oxazoline compounds, aziridine compounds, carbodiimide compounds, metal chelate compounds, butylated melamine compounds, etc., taking into account the reactivity with the functional group possessed by the polymer in the adhesive. For example, in the case of containing hydroxyl groups as the functional groups of the polymer in the adhesive, isocyanate compounds can be used.

[0089] The isocyanate compound is an isocyanate having two or more isocyanate groups. The isocyanate compound is preferably an isocyanate monomer such as aromatic polyisocyanate, aliphatic polyisocyanate, aromatic aliphatic polyisocyanate, alicyclic polyisocyanate, and a burette body, urate body, and adduct thereof.

[0090] Examples of the aromatic polyisocyanate include 1,3-phenylene diisocyanate, 4,4′-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4′-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4′-toluidine diisocyanate, 2,4,6-triisocyanatotoluene, 1,3,5-triisocyanatobenzene, dianisidine diisocyanate, 4,4′-diphenyl ether diisocyanate, and 4,4′,4″-triphenylmethane triisocyanate.

[0091] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HMDI (hexamethylene diisocyanate)), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0092] Examples of the aromatic aliphatic polyisocyanate include ω,ω′-diisocyanate-1,3-dimethylbenzene, ω,ω′-diisocyanate-1,4-dimethylbenzene, ω,ω′-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.

[0093] Examples of the alicyclic polyisocyanate include 3-isocyanate methyl-3,5,5-trimethylcyclohexyl isocyanate (also known as IPDI (isophorone diisocyanate), isophorone diisocyanate), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4′-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanate methyl)cyclohexane.

[0094] The burette body is a self-condensate having a burette bond formed by self-condensation of an isocyanate monomer. Examples of the burette body include a burette body of hexamethylene diisocyanate.

[0095] The urate body is a trimer of an isocyanate monomer, and examples thereof include a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate, and a trimer of toluene diisocyanate.

[0096] The adduct is a difunctional or higher isocyanate compound formed by reacting an isocyanate monomer with a difunctional or higher compound containing low molecular active hydrogen. Examples of the adduct include a compound formed by reacting trimethylolpropane with hexamethylene diisocyanate, a compound formed by reacting trimethylolpropane with toluene diisocyanate, a compound formed by reacting trimethylolpropane with xylylene diisocyanate, a compound formed by reacting trimethylolpropane with isophorone diisocyanate, a compound formed by reacting 1,6-hexanediol with hexamethylene diisocyanate, and the like.

[0097] From the viewpoint of forming a sufficient cross-linked structure, the isocyanate compound is preferably a trifunctional isocyanate compound. The isocyanate compound is more preferably an adduct of a reaction product of an isocyanate monomer and a trifunctional compound containing low molecular active hydrogen, and a urate body. The isocyanate compound is preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a urate body of hexamethylene diisocyanate, a trimethylolpropane adduct of toluene diisocyanate, a urate body of toluene diisocyanate, a trimethylolpropane adduct of isophorone diisocyanate, and a urate body of isophorone diisocyanate, more preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of toluene diisocyanate, and a trimethylolpropane adduct of isophorone diisocyanate.

[0098] Examples of the epoxy compound include glycerol diglycidyl ether, 1,6-hexanediol diglycidyl ether, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidylaminophenylmethane.

[0099] Examples of the aziridine compound include N,N′-diphenylmethane-4,4′-bis(1-carbonylaziridine), tris-2,4,6-(1-aziridinyl)-1,3,5-triazine, and 4,4′-bis(ethyleneiminocarbonylamino)diphenylmethane.

[0100] The carbodiimide compound is preferably a high molecular weight polycarbodiimide generated by subjecting a diisocyanate compound to a decarbonation condensation reaction in the presence of a carbodiimidization catalyst. The commercially available product of the high molecular weight polycarbodiimide is preferably the Carbodilite series of Nissinbo Co., Ltd. Among them, Carbodilite V-03, 07, and 09 are preferably preferred due to their excellent compatibility with organic solvents.

[0101] The metal chelate is preferably a coordination compound of a polyvalent metal such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium with acetylacetone or ethyl acetylacetate. Examples of the metal chelate include ethyl acetylacetate aluminum-diisopropyl alcohol ester, aluminum triacetylacetonate, bisethyl acetylacetate aluminum-monoacetylacetonate, and alkyl acetylacetate aluminum-diisopropyl alcohol ester.

[0102] The curing agent preferably contains 0.02 to 4.0 parts by mass, more preferably 0.04 to 1.0 parts by mass, and further preferably 0.04 to 0.4 parts by mass, relative to 100 parts by mass of the acrylic copolymer in the adhesive. If the content is 0.02 parts by mass or more, the cohesive force is further improved, and if the content is 4 parts by mass or less, it is easy to achieve both cohesive force and flexibility, so it is preferred.

[0103] The acrylic adhesive may contain, in addition to the silane coupling agent and chlorinated polyolefin described below, various resins, oils, softeners, dyes, pigments, antioxidants, ultraviolet absorbers, weather stabilizers, plasticizers, fillers, antioxidants, anti-aging agents, antistatic agents, and the like as optional components as long as the problem can be solved.

[0104] Examples of methods for adjusting the polarity component of the adhesive layer to 0.5 mN / m or less include a method of reducing the polarity of the resin used in the adhesive and a method of adding a low-polarity additive that is preferentially present on the surface after coating.

[0105] For example, in order to reduce the polarity of the acrylic copolymer, the ratio of (meth)acrylic acid alkyl esters having an alkyl group with 1 to 3 carbon atoms, hydroxyl-containing monomers, acid-containing monomers, amide-containing monomers, amino-containing monomers, oxyalkylene-containing monomers, or monomers copolymerizable with acrylic monomers other than these, having a water / octanol partition coefficient log Kow of 2.22 or less at 25° C., and monomers miscible with water can be reduced, and the ratio of (meth)acrylic acid alkyl esters having an alkyl group with 4 or more carbon atoms can be increased.

[0106] Specifically, the (meth)acrylic acid alkyl ester having an alkyl group having 1 to 3 carbon atoms is preferably 25% by mass or less, more preferably 20% by mass or less, more preferably 18% by mass or less, and still more preferably 15% by mass or less in 100% by mass of the acrylic copolymer.

[0107] The hydroxyl group-containing monomer is preferably 5% by mass or less, and more preferably 2% by mass or less in 100% by mass of the acrylic copolymer.

[0108] The acid-containing monomer is preferably 5% by mass or less, more preferably 2% by mass or less, and most preferably 1% by mass or less in 100% by mass of the acrylic copolymer.

[0109] The amount of the amide group-containing monomer in 100% by mass of the acrylic copolymer is preferably less than 5% by mass, more preferably 3% by mass or less, and most preferably 1% by mass or less.

[0110] The amino group-containing monomer is preferably less than 5% by mass, more preferably 3% by mass or less, and most preferably 1% by mass or less in 100% by mass of the acrylic copolymer.

[0111] The ratio of the oxyalkylene group-containing monomer is preferably less than 20% by mass, more preferably 10% by mass or less, and most preferably 5% by mass or less.

[0112] Among other monomers copolymerizable with the acrylic monomer, the content of monomers having a water / octanol partition coefficient log Kow of 2.22 or less at 25°C and monomers miscible with water is preferably less than 10% by mass, more preferably 5% by mass or less, further preferably 3% by mass or less, and most preferably 1% by mass or less.

[0113] The monomers described in the above paragraphs may each account for 0% by mass or more (that is, may also account for 0% by mass) in 100% by mass of the acrylic copolymer.

[0114] The (meth)acrylic acid alkyl ester having an alkyl group with 4 or more carbon atoms is preferably 80% by mass or more, more preferably 85% by mass or more in 100% by mass of the acrylic copolymer.

[0115] Examples of a method for preparing a low-polarity additive that is preferentially present on the surface after coating include a method of adding a silane coupling agent, a chlorinated polyolefin, or a combination of these to the adhesive.

[0116] The amount of these low-polarity additives blended individually or in total is preferably 0.05 to 0.5 parts by mass, more preferably 0.1 to 0.3 parts by mass, per 100 parts by mass of the resin component of the acrylic copolymer.

[0117] In this case, the polar term component of the surface free energy of the acrylic copolymer before the low polarity additive is formulated (ie, without the addition of the low polarity additive) is preferably 2.0 mN / m or less, more preferably 1.5 mN / m or less.

[0118] Examples of the silane coupling agent include alkoxysilane compounds having a (meth)acryloyloxy group, alkoxysilane compounds having a vinyl group, alkoxysilane compounds having an amino group, alkoxysilane compounds having a mercapto group, and alkoxysilane compounds having an epoxy group.

[0119] Specific examples of commercially available products include KBM403 (3-glycidyloxypropyltrimethoxysilane), KBE403 (3-glycidyloxypropyltriethoxysilane), KBM303 (2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane) (all manufactured by Shin-Etsu Chemical Co., Ltd.), and BYK-325N (polyether-modified polymethylalkylsiloxane) (manufactured by BYK-Chemie Japan Co., Ltd.).

[0120] Examples of the chlorinated polyolefin include chlorinated polypropylene, acid-modified chlorinated polypropylene, acrylic acid-modified chlorinated polypropylene, chlorinated polyethylene, and chlorinated ethylene vinyl acetate (EVA) copolymers. Chlorinated polypropylene and chlorinated ethylene vinyl acetate copolymers are preferred because they have good compatibility with acrylic copolymers and can effectively reduce polarity.

[0121] Specific examples of commercially available products include superchlon 390S (chlorinated polypropylene, chlorine content 36%) and superchlon BX (chlorinated EVA, chlorine content 18%) (both manufactured by Nippon Paper Industries, Ltd.).

[0122] 《Laminate for flexible display》

[0123] The laminate for flexible display includes an adhesive layer on a light-transmitting flexible substrate. For example, it has a structure of substrate / adhesive layer / polarizing plate. Preferably, it includes a light-transmitting flexible substrate, an adhesive layer, and a polarizing plate in sequence. Thus, a laminate with excellent transparency and bendability is formed.

[0124] Figure 1 An example of a schematic cross-sectional view partially showing a laminated body according to an embodiment of the present disclosure is shown. Figure 1 In the figure, 3 is a light-transmitting flexible substrate (cover plate), 1 is an adhesive layer, and 4 is a polarizing plate.

[0125] exist Figure 1 In the laminate shown, a light-transmitting flexible substrate (cover plate) is attached to a polarizing plate via an adhesive layer.

[0126] [Light-transmitting flexible substrate]

[0127] As the light-transmitting flexible substrate (cover substrate), a transparent plastic substrate can be used.

[0128] In the present disclosure, the polar term component of the surface free energy of the light-transmitting flexible substrate is 3.0 mN / m or more, preferably 4.0 mN / m or more. The close contact caused by the polar attraction between the adhesive layer having a polar term component of less than 0.5 mN / m and the light-transmitting flexible substrate having a polar term component of more than 3.0 mN / m is not too strong, and the adhesive layer follows the movement of the substrate during repeated bending, and it is not easy to produce whitening of the bent portion or displacement of the adherends caused by the adhesive layer. If a light-transmitting flexible substrate having a polar term component of more than 4.0 mN / m is used, the effect of the present disclosure is more excellent, so it is preferred. The upper limit of the polar term component of the surface free energy of the light-transmitting flexible substrate is not particularly limited, but typically it is less than 10 mN / m.

[0129] As the raw material of such a light-transmitting flexible substrate, for example, acrylic resins such as polyethylene terephthalate (PET) and polymethyl methacrylate (PMMA), polycarbonate, polycycloolefin, polyimide and other plastic materials can be cited. PET film or polyimide is particularly preferred, and polyimide is most preferred in terms of durability. The plastic material can be used alone or in combination of two or more.

[0130] Since the adhesive layer used in the laminate of the present disclosure has excellent bending resistance, even when a colorless polyimide obtained by making the polyimide transparent is used for the substrate, a laminate in which the displacement or whitening of adherends is suppressed can be obtained.

[0131] As the light-transmitting flexible substrate (cover sheet), among the above-mentioned transparent plastic substrates, a transparent plastic substrate having excellent heat resistance, that is, a transparent plastic substrate which suppresses or prevents deformation under severe conditions such as high temperature or high temperature and high humidity, can also be preferably used.

[0132] The light-transmitting flexible substrate may be subjected to surface treatments such as plasma treatment, corona treatment, frame treatment, and UV treatment as required. Even transparent plastic substrates such as polyethylene (PE) and polypropylene (PP) whose polarity component value is less than 3.0 mN / m when untreated can be set to a value of 3.0 mN / m or more by performing the surface treatment, and can be used in the embodiments of the present disclosure.

[0133] The thickness of the light-transmitting flexible substrate is not particularly limited, but is, for example, preferably 100 μm to 2000 μm, and more preferably 200 μm to 1000 μm.

[0134] <Manufacturing of laminated body for flexible display>

[0135] Regarding the method for manufacturing the laminate, for example, the release films can be peeled off from an adhesive sheet having release films on both sides of the adhesive layer, and the adhesive layers can be attached to adherends such as a light-transmitting flexible substrate or a polarizing plate to form the laminate. Alternatively, the adhesive layer can be directly formed on the light-transmitting flexible substrate, and then an adherend or an adhesive layer included in another adhesive sheet can be attached to the adhesive layer to form the laminate.

[0136] [Adhesive sheet]

[0137] The adhesive sheet can be manufactured by a common manufacturing method. For example, the following methods can be used to manufacture the adhesive sheet: a method in which an adhesive is directly applied to one side of a release film so that the thickness after drying becomes a predetermined thickness to form an adhesive layer, and another release film is attached thereto; or a method in which an adhesive is applied to one side of two release films so that the thickness after drying becomes a predetermined thickness to form two adhesive layers, and the adhesive layers are attached to each other.

[0138] When applying the adhesive, a conventional coater such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a rod coater, a knife coater, or a spray coater can be used.

[0139] The adhesive sheet may be cut into a suitable width and wound into a roll to have a form of an adhesive tape wound into a roll.

[0140] The thickness of the adhesive layer is not particularly limited, and is preferably 10 μm to 500 μm, more preferably 50 μm to 200 μm. If the thickness of the adhesive layer is 10 μm to 500 μm, sufficient cohesion can be easily obtained, the end of the adhesive layer is not offset or exposed, and the bendability during high-speed bending can be taken into account, so it is preferred.

[0141] The mass per unit area of ​​the adhesive layer (hereinafter also referred to as the coating amount) is 10 g / m 2 ~100g / m 2 , preferably 25g / m 2 ~70g / m 2 By setting the mass per unit area of ​​the adhesive layer to the above range, it is possible to obtain an adhesive layer in which the bent portion does not whiten and the adherends do not shift with each other even when bent repeatedly. 2 When the coating amount is 100 g / m, the adhesive layer can sufficiently follow the adherend during bending, and the occurrence of end deviation caused by floating can be further suppressed. 2 Thereby, it is possible to further suppress the adhesive layer from being exposed from the end portion when being bent.

[0142] The release film is not particularly limited, and a transparent plastic substrate can be preferably used. Examples of the raw materials of the transparent plastic substrate include polyesters such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose, polysulfone, polyarylate, polycycloolefin and other plastic materials. In addition, the plastic material can be used alone or in combination of two or more.

[0143] As the release film, among the above-mentioned transparent plastic substrates, a transparent plastic substrate having excellent heat resistance, that is, a transparent plastic substrate which is suppressed or prevented from deforming under severe conditions such as high temperature or high temperature and high humidity, can be preferably used.

[0144] The release film may have any form of a single layer or a multilayer. In addition, the surface of the transparent substrate may be subjected to appropriate surface treatments such as physical treatments such as corona discharge treatment and plasma treatment, and chemical treatments such as primer treatment.

[0145] Flexible Display

[0146] The flexible display preferably includes the laminate of the present disclosure and an optical element. Thus, the display of the present disclosure has excellent bendability and visibility. For example, the optical element can be attached to the polarizing plate of the laminate via another adhesive layer.

[0147] The optical element is not particularly limited, and examples thereof include a liquid crystal element and an organic EL element.

[0148] Figure 2 , which partially shows an example of a schematic cross-sectional view of a display as an example of use of the adhesive sheet of the present disclosure. Figure 2 3 is a light-transmitting flexible substrate (cover plate), 1 is a first adhesive layer, 4 is a polarizing plate, 5 is a second adhesive layer, 6 is a barrier layer such as silicon nitride, 7 is an organic EL layer, 8 is a support such as polyimide, and 9 is an organic EL unit. In addition, the structure of the display is not limited to Figure 2 .

[0149] exist Figure 2 In the display shown, the light-transmitting flexible substrate (cover plate) is attached to the polarizing plate via the adhesive layer (first adhesive layer) of the present disclosure, and further attached to the organic EL unit via the adhesive layer for the polarizing plate (second adhesive layer). In this way, the adhesive sheet of the present disclosure can be attached to the light-transmitting flexible substrate (cover plate) and the polarizing plate using a transparent adhesive layer formed by the adhesive, and further attached to the laminated body to the organic EL via the adhesive layer for the polarizing plate.

[0150] For example, in Figure 2 In the embodiment of the present invention, the adhesive layer of the present invention can be used for any one of the first adhesive layer and the second adhesive layer.

[0151] Generally speaking, when comparing the first adhesive layer with the second adhesive layer, the first adhesive layer has higher requirements for the quality of the adhesive layer. The adhesive disclosed in the present invention has good adhesion and adhesion to the substrate, so it is preferably used for the first adhesive layer. At this time, the adhesive used to form the second adhesive layer can use the adhesive disclosed in the present invention or a previously known adhesive.

[0152] The use of the display is not particularly limited, and examples thereof include organic EL televisions, organic EL smartphones, organic EL tablets, and organic EL smart watches.

[0153] Example

[0154] Next, examples are shown to further illustrate the details, but the present invention is not limited thereto. In the examples, unless otherwise specified, "parts" means "parts by mass", "%" means "mass %", and "RH" means relative humidity. In addition, the amounts in the table are parts by mass. In addition, the blanks in the table indicate that the corresponding components are not mixed.

[0155] In addition, the method for measuring the mass average molecular weight of the acrylic copolymer is as follows.

[0156] <Measurement of Mass Average Molecular Weight of Acrylic Copolymer>

[0157] The mass average molecular weight (Mw) can be measured using GPC "LC-GPC System" manufactured by Shimadzu Corporation, and can be performed by conversion using polystyrene having a known molecular weight as a standard substance.

[0158] Device name: LC-GPC system "Prominence" manufactured by Shimadzu Corporation

[0159] Pipe string: Four GMHXL pipes manufactured by Tosoh and one HXL-H pipe manufactured by Tosoh are connected.

[0160] Mobile phase solvent: tetrahydrofuran

[0161] Flow rate: 1.0ml / min

[0162] Column temperature: 40℃

[0163] <Production Example of Acrylic Copolymer>

[0164] (Acrylic copolymer (R9))

[0165] In a reaction container (hereinafter simply referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, a dripping device, and a nitrogen introduction tube, 20 parts of methyl acrylate (MA), 43.2 parts of 2-ethylhexyl acrylate (2EHA), 35 parts of dodecyl acrylate (DOA), 1 part of 4-hydroxybutyl acrylate (4HBA), 0.8 parts of acrylic acid (AA), and 0.2 parts of 2,2'-azobisisobutyronitrile (2,2'-azobisisobutyronitrile) (hereinafter simply referred to as "AIBN") as an initiator were placed, and the atmosphere in the reaction container was replaced with nitrogen. Then, the reaction was started by heating to 50°C while stirring under a nitrogen atmosphere. Then, the reaction solution was reacted at 50°C for 4 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain a copolymer (R9) solution having a nonvolatile content of 30%. The mass average molecular weight of the obtained copolymer (R9) was 890,000.

[0166] (Acrylic copolymer (R10-R11, R35-R62)

[0167] Acrylic copolymers (R10 to R11, R35 to R62) were produced by the same method as that for producing the acrylic copolymer (R9), except that the composition and the blending amount (parts by mass) were changed to those described in Table 1.

[0168] Tables 1, 2, and 3 show the compositions, blending amounts (non-volatile mass fractions), and mass average molecular weights (Mw) of the obtained acrylic copolymers (R9 to R11, R35 to R62).

[0169] [Table 1]

[0170] Table 1

[0171]

[0172]

[0173] [Table 3]

[0174] Table 3

[0175]

[0176] The abbreviations in the table are as follows.

[0177] MA: Methyl acrylate (the carbon number of the alkyl group is 1)

[0178] EA: Ethyl acrylate (the carbon number of the alkyl group is 2)

[0179] 2EHA: 2-ethylhexyl acrylate (alkyl carbon number 8)

[0180] BA: Butyl acrylate (alkyl carbon number 4)

[0181] DOA: dodecyl acrylate (alkyl carbon number 12)

[0182] IBXA: Isobornyl acrylate (the carbon number of the alkyl group (ring structure) is 10)

[0183] TDA: Tridecyl acrylate (alkyl carbon number 13)

[0184] IBXMA: Isobornyl methacrylate (the carbon number of the alkyl group (ring structure) is 10)

[0185] nHA: n-heptyl acrylate (alkyl carbon number 7)

[0186] IAA: Isoamyl acrylate (the carbon number of the alkyl group (branched) is 5)

[0187] 4HBA: 4-Hydroxybutyl acrylate

[0188] 2HEA: 2-Hydroxyethyl Acrylate

[0189] AA: Acrylic acid

[0190] DMAEA: 2-Dimethylaminoethyl acrylate

[0191] ACMO: Acryloylmorpholine MDEA: Methoxydiethylene glycol acrylate

[0192] a1: (meth)acrylic acid alkyl ester monomer having an alkyl group with 1 to 3 carbon atoms

[0193] a2: (meth)acrylic acid alkyl ester monomer having an alkyl group with 4 or more carbon atoms

[0194] a3: Monomer containing hydroxyl groups

[0195] a4: Acid-containing monomer

[0196] a5: Monomers containing amino groups

[0197] a6: Monomer containing amide group

[0198] a7: Monomer containing oxyalkylene

[0199] (Example 1)

[0200] <Preparation of adhesive>

[0201] To 100 parts of the nonvolatile components of the acrylic copolymer (R9), 0.14 parts of a trimethylolpropane adduct of hexamethylene diisocyanate D-160N as a curing agent and 0.1 parts of KBM-403 as a low-polarity additive were added, and ethyl acetate was further prepared so that the nonvolatile component became 20%, and the mixture was stirred to obtain an adhesive.

[0202] <Adhesive Sheet Production>

[0203] The adhesive was applied to a 75 μm thick polyethylene terephthalate separator (release film 1) to a thickness of 50 μm after drying, and dried with hot air at 100° C. for 2 minutes to form an adhesive layer. Subsequently, a 50 μm thick polyethylene terephthalate separator (release film 2) was bonded to the adhesive layer to obtain a first adhesive sheet.

[0204] <Production of laminated body>

[0205] One of the diaphragms is peeled off from the adhesive sheet, and the exposed adhesive layer is attached to CPI (colorless polyimide, manufactured by KOLON, 50 μm, polarity component of 4.5 mN / m) as a translucent flexible substrate under an environment of 25°C and 50% relative humidity using a laminator. The other diaphragm is peeled off and attached to a PET film with a thickness of 188 μm using a laminator to obtain a laminate of PET film / adhesive layer / translucent flexible substrate.

[0206] (Example 2 to Example 40, Comparative Example 1 to Comparative Example 12)

[0207] As shown in Tables 4 to 7, the types and amounts (parts by mass) of the acrylic copolymer, the curing agent, and the additives were changed, and an adhesive sheet was obtained in the same manner as in Example 1. Then, an adhesive layer was attached to the light-transmitting flexible substrate shown in Tables 4 to 7 to obtain a laminate of PET film / adhesive layer / light-transmitting flexible substrate.

[0208] 《Evaluation of adhesive layer》

[0209] The physical properties of the adhesive layer and the laminate were measured and evaluated by the following methods. The results are shown in Tables 4 to 7.

[0210] <Measurement of the mass per unit area of ​​the adhesive layer (coating amount)>

[0211] The obtained adhesive sheet was cut into a size of 100 mm × 100 mm, and the mass (mass W (g)) was measured. In addition, a polyethylene terephthalate separator (peel film 1) with a thickness of 75 μm and a polyethylene terephthalate separator (peel film 2) with a thickness of 50 μm used for the adhesive sheet were cut into a size of 100 mm × 100 mm, and the mass was measured (mass W75 (g) and mass W50 (g) respectively).

[0212] Coating amount (g / m 2 )=(W-W75-W50) / 0.01

[0213] <Measurement of gel fraction>

[0214] The obtained adhesive sheet was cut into a size of 30 mm × 100 mm, and the adhesive layer exposed by peeling off the polyethylene terephthalate separator (peeling film 2) with a thickness of 50 μm was attached to a weighed 300-mesh stainless steel metal mesh (mass W0), and then the polyethylene terephthalate separator (peeling film 1) with a thickness of 75 μm was peeled off to prepare a sample. The mass of the weighed sample was set as W1, and the mass of the sample after standing in ethyl acetate for 24 hours, drying at 100°C for 1 hour and weighing was set as W2, and the following formula was used to calculate.

[0215] Gel fraction (%) = {(W2-W0) / (W1-W0)}×100

[0216] <Determination of polar component of surface free energy>

[0217] The polyethylene terephthalate separator (release film 2) having a thickness of 50 μm was peeled off from the obtained adhesive sheet to expose the adhesive layer and perform measurement.

[0218] The measurement was performed using MSA manufactured by KRUSS, and the polarity term was determined by calculating the contact angle 1 second after 1 μl of each of water and diiodomethane was landed on the adhesive layer or the light-transmitting flexible substrate using the OWRK method.

[0219] <Evaluation of whitening of the bent portion, deviation of the end portion, and exposure of the end portion by the standard bending test>

[0220] The obtained laminate was used as a normal test. A bending tester (manufactured by Yuasa System Machinery Co., Ltd.) was used in an environment of 25°C and a relative humidity of 50%. The inner diameter (diameter) during bending was set to 3 mm, and bending and opening 180° were set as one cycle. 30 cycles were repeated at a speed of 30 reciprocating times per minute.

[0221] The appearance after the test was evaluated for whitening of the bent portion and deviation of the edge of the adherend using the following criteria. The higher the numerical value of the evaluation criteria, the better, and a value of 3 or more is considered practical.

[0222] Appearance: The presence or absence of bubbles in the test laminate, the presence or absence of misalignment of the edges of the adherends, and the presence or absence of protrusion of the edge of the adhesive layer were visually evaluated under the following conditions.

[0223] [Whitening of the curved part]

[0224] 5: No bubbles were found within 5 mm on both sides of the bending part.

[0225] 4: There are 1 or more and 10 or less bubbles within the range of 5 mm to the left and right of the curved portion.

[0226] 3: The number of bubbles within the range of 5 mm to the left and right of the curved portion is 11 or more and 50 or less.

[0227] 2: The number of bubbles within the range of 5 mm to the left and right of the curved portion is 51 or more and 100 or less.

[0228] 1: There are 100 or more bubbles within the range of 5 mm on both sides of the bending part.

[0229] [End offset]

[0230] 5: The displacement between the PET film and the light-transmitting flexible substrate is less than 1 mm.

[0231] 4: The displacement between the PET film and the light-transmitting flexible substrate is 1 mm or more and less than 2 mm.

[0232] 3: The displacement between the PET film and the light-transmitting flexible substrate is 2 mm or more and less than 3 mm.

[0233] 2: The displacement between the PET film and the light-transmitting flexible substrate is 3 mm or more and less than 4 mm.

[0234] 1: The displacement between the PET film and the light-transmitting flexible substrate is 4 mm or more.

[0235] [Exposure of the end]

[0236] 5: The exposure from the edge of the adhesive layer is less than 100 μm.

[0237] 4: The exposure from the edge of the adhesive layer is 100 μm or more and less than 200 μm.

[0238] 3: The exposure from the edge of the adhesive layer is 200 μm or more and less than 300 μm.

[0239] 2: The exposure from the edge of the adhesive layer is 300 μm or more and less than 400 μm.

[0240] 1: The exposure from the edge of the adhesive layer is 400 μm or more.

[0241] <Evaluation of whitening of the bent portion, displacement of the end portion, and exposure of the end portion by high-speed bending test>

[0242] The test was conducted at a reciprocating speed of 120 times per minute and a cycle number of 100,000 cycles of the standard bending test, and the evaluation was conducted based on the same evaluation criteria as the standard bending test.

[0243] [Table 4]

[0244] Table 4

[0245]

[0246]

[0247]

[0248] [Table 7]

[0249] Table 7

[0250]

[0251] The abbreviations in the table are as follows.

[0252] <Hardener>

[0253] D-110N: Trimethylolpropane adduct of xylylene diisocyanate

[0254] D-160N: Trimethylolpropane adduct of hexamethylene diisocyanate

[0255] EX-313: Multifunctional epoxy compound (glycerol polyglycidyl ether)

[0256] D-370N: Isocyanurate of 1,5-pentamethylene diisocyanate

[0257] DID: trimethylolpropane adduct of decamethylene diisocyanate

[0258] <Additives>

[0259] KBM-403: Epoxy silane KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd.

[0260] KBE-403: Epoxy silane KBE-403 manufactured by Shin-Etsu Chemical Co., Ltd.

[0261] KBM-303: Epoxy silane KBM-303 manufactured by Shin-Etsu Chemical Co., Ltd.

[0262] BYK-325N: BYK-Chemie Japan Co., Ltd. manufactures silicon-containing surface conditioning agent BYK-325N

[0263] 390S: Chlorinated polyolefin 390S manufactured by Nippon Paper Industries, Ltd.

[0264] BX: Chlorinated EVABX manufactured by Nippon Paper Industries, Ltd.

[0265] <Light-transmitting flexible substrate>

[0266] CPI: Colorless polyimide (manufactured by KOLON, 50 μm, polar component 4.5 mN / m)

[0267] P-CPI: Colorless polyimide after plasma treatment (the CPI is treated, 50 μm, polar component 7.6 mN / m))

[0268] PET: Polyethylene terephthalate (manufactured by Toyobo Co., Ltd., 50 μm, polar component 5.8 mN / m)

[0269] PMMA: polymethyl methacrylate (manufactured by Mitsubishi Chemical Corporation, 53 μm, polar component 6.8 mN / m)

[0270] C-HDPE: Corona treated high-density polyethylene (manufactured by NT Film Co., Ltd., 50 μm) (polarity component 4.8 mN / m)

[0271] C-OPP: Corona treated stretched polypropylene (manufactured by Toyobo Co., Ltd., 40 μm) (polar component 4.6 mN / m)

[0272] In the corona treatment when making C-HDPE and C-OPP, a corona treatment device plasma dyne manufactured by Navitas was used, the speed was set to 100 mm / sec, the distance between the corona discharge nozzle and the substrate was set to 20 mm, and the corona discharge nozzle was scanned once from one end to the other end of the substrate.

[0273] According to the results of Tables 4 to 7, the adhesive layer of the present disclosure does not cause the offset of the adherends after bonding even if it is repeatedly bent, and the adhesive layer does not expose from the end. In addition, it is confirmed that even when a colorless polyimide is used as a light-transmitting flexible substrate, the bent portion will not whiten due to foaming. Thus, the display including the laminate having the adhesive layer of the present disclosure has excellent bendability, thereby obtaining a display with excellent visibility.

[0274] On the other hand, the adhesive layers of Comparative Examples 1 to 12 could not satisfy all the above characteristics.

[0275] Explanation of symbols

[0276] 1: First adhesive layer

[0277] 3: Translucent flexible substrate (cover)

[0278] 4: Polarizing plate

[0279] 5: Second adhesive layer

[0280] 6: Barrier layer

[0281] 7: Organic EL layer

[0282] 8: Support body

[0283] 9: Organic EL unit

Claims

1. A laminate for a flexible display, comprising an adhesive layer on a light-transmitting flexible substrate, wherein the laminate for a flexible display is characterized in that: The polar component of the surface free energy of the light-transmitting flexible substrate calculated based on the Euwin-Laquet method from the contact angle of water and the contact angle of diiodomethane is 3.0 mN / m or more, The polar component of the surface free energy of the adhesive layer calculated based on the Euwin-Laquet method from the contact angle of water and the contact angle of diiodomethane is 0.5 mN / m or less, The mass per unit area of ​​the adhesive layer is 10 g / m 2 ~100g / m 2 , The adhesive layer is formed of an acrylic adhesive. The acrylic adhesive comprises: an acrylic copolymer, wherein, in 100% by mass of the acrylic copolymer, 25% by mass or less of repeating units derived from a hydroxyl-containing monomer, 10% by mass or less of repeating units derived from an acid-containing monomer, 15% by mass or less of repeating units derived from an amide-containing monomer, 15% by mass or less of repeating units derived from an amino-containing monomer, and 75% to 90% by mass of repeating units derived from an alkyl (meth)acrylate having an alkyl group with 4 or more carbon atoms are contained; and a low-polarity additive.

2. The laminate for a flexible display according to claim 1, wherein: The polar component of the surface free energy of the adhesive layer calculated based on the Eugene-Laquet method from the contact angle of water and the contact angle of diiodomethane is 0.2 mN / m or less.

3. The laminate for a flexible display according to claim 1, wherein: The mass per unit area of ​​the adhesive layer is 25 g / m 2 ~70g / m 2 , and the gel fraction of the adhesive layer is 60% to 80% by mass.

4. The laminate for a flexible display according to claim 1, wherein: The curing agent is contained in an amount of 0.02 to 4.0 parts by mass based on 100 parts by mass of the acrylic copolymer. 5 . The laminate for a flexible display according to claim 1 , further comprising a polarizing plate on the adhesive layer.

6. A flexible display comprising the laminated body according to claim 5, and an optical element.

Citation Information

Patent Citations

  • Adhesive resin composition, adhesive resin cured product, adhesive sheet, and image display device laminate

    JP2020097737A

  • Optically transparent adhesive sheet, composition for manufacturing the same, and flat panel display device using the same

    JP2020517800A